A5 noradrenergic neurons and breathing control in neonate rats - Taxini, Camila L. [UNESP]; Marques, Danuzia A.; Bícego, Kênia C. [UNESP]; Gargaglioni, Luciane H. [UNESP] (Springer Nature, 2021)
The pontine A5 noradrenergic group contributes to the maturation of the respiratory system before birth in rats. These neurons are connected to the neural network responsible for respiratory rhythmogenesis. In the present study, we investigated the participation of A5 noradrenergic neurons in neonates (P7–8 and P14–15) in the control of ventilation during hypoxia and hypercapnia in in vivo experiments using conjugated saporin anti-dopamine beta-hydroxylase (DβH-SAP) to specifically ablate noradrenergic neurons. Thus, DβH-SAP (420 ng/μL) or saporin (SAP, control) was injected into the A5 region of neonatal male Wistar rats. Hypoxia reduced respiratory variability in control animals; however, A5 lesion prevented this effect in P7–8 rats. Our data suggest that noradrenergic neurons of the A5 region in neonate rats do not participate in the control of ventilation under baseline and hypercapnic conditions, but exert an inhibitory modulation on breathing variability under hypoxic challenge in early life (P7–8).
Keywords: Brainstem; Catecholaminergic neurons; Development; Hypercapnia; Hypoxia